2019
DOI: 10.1111/jfbc.12756
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and ability to prevent acrylamide formation in fried foods of asparaginase from soybean root nodules

Abstract: A novel asparaginase (designated srnASNase) has been purified from soybean root nodules and identified by MALDI‐TOF/TOF‐MS. And the enzymatic properties, antitumor activity and the ability to prevent acrylamide formation in fried foods of srnASNase were evaluated. SrnASNase had high specific activity (531.37 U/mg) toward L‐asparagine under optimum conditions (pH 8.0 and 40°C), no activity toward L‐glutamine and D‐glutamine, but trace activity toward D‐asparagine. It was stable in the pH range of 7.0–9.0 and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The pre-processing method before frying such as blanching, addition of salts, soaking, addition of vinegar, organic acids, and antioxidants has also been discovered for acrylamide mitigation. Use of enzymes, such asparaginase, to prevent the formation of acrylamide through the enzymatic conversion of L-asparagine to ammonia and L-aspartic acid has also been observed as a mitigation technique [ 10 ]. However, even when produced from diffused and renewable sources, the price of enzymes remains expensive [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-processing method before frying such as blanching, addition of salts, soaking, addition of vinegar, organic acids, and antioxidants has also been discovered for acrylamide mitigation. Use of enzymes, such asparaginase, to prevent the formation of acrylamide through the enzymatic conversion of L-asparagine to ammonia and L-aspartic acid has also been observed as a mitigation technique [ 10 ]. However, even when produced from diffused and renewable sources, the price of enzymes remains expensive [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this information is not supported by sequence databases, as the B. licheniformis genome does not encode an L-asparaginase with such a high M w . It was also shown that an enzyme isolated from soybean root nodules (K m for L-Asn 0.36 mM) had higher antiproliferative activity in MOLT-4 and HL-60 cells than EcAII [56]. It is possible that the extracted protein was a thermolabile class 3 L-asparaginase.…”
Section: Discussionmentioning
confidence: 99%
“…response induced by the higher glutaminase activity of the EcA drug, such as the screening of L-ASNase from bacteria, fungi, and yeast, for high throughput. 18,[67][68][69][70][71][72] At the same time, researchers are not only exploring possible sources of production, but also experimenting with different immobilization methods to enhance therapeutic efficacy, such as the novel p(HEMA-GMA) cryogel invented by Noma et al which resulted in a significant increase in enzyme activity and stability, and Ca-ALG/MWCNT-COOH hybrid beads designed by Ulu et al which enhanced the affinity of the enzyme for the substrate. [73][74][75] 4.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%